Hoofdartikelen uit De Fabrieksbode, 1882-1905. - Van Marken, J.C. (Delft : Van Marken, 1905)
Bibliotheek E. Anseele
Omslagtitel : Uit het fabrieksleven, Delft 1869-1905
AANWEZIG: delen 1-3
Nederlands
Meerdelige publicatie